Hubungan Pola Pemberian Makan Dengan Kejadian Stunting Pada Balita - fauziah, Rahma; Farming , Farming; hikmandayani, Hikmandayani; kartini, kartini; Ekawati Mihora, Dian Putri (Jurnal Stunting Pesisir dan Aplikasinya, 2023)
Introduction: Stunting in children is defined as an acute nutritional problem caused by the intake of nutrients that enter the body do not meet the standards for a long time. This condition can occur starting from the child is still in the womb and the effect is only seen when he was 2 years old. Usually children who are stunted get less food intake in accordance with the nutritional intake needed at their age, so that growth becomes less optimal.Objective: the purpose of this review literature is to determine the relationship between feeding patterns and the incidence of stunting. Methods: Literature reviews are conducted based on issues, metologies, equations and research journals. Of the 5 journals used, each used a cross sectional method. Results: based on 5 articles using the cross sectional method and case control parenting feeding sta toddlers stunting does not match the nutritional needs of toddlers. The relationship between feeding patterns and stunting events.If the wrong feeding patterns and inadequate food diversity can cause stunting in toddlers.Conclusion: parenting giving the wrong toddler has the potential to cause stunting